Development of interactive sport measurement test learning media - Afri Tantri; Abdul Hakim Siregar; Nurman Hasibuan; Benny Aprial. M (Jurnal Keolahragaan, 2023)
Media is one of the factors that support the success of the learning process, but there are still several shortcomings in the use of media to support learning. The aim of this research is to produce learning media in the physical education measurement test subject based on interactive multimedia, with product results in the form of mobile applications, interactive VCDs, printed books, and indexed reputable international journals which will later be used both in learning activities and in independent learning to facilitate in delivering learning material for physical education measurement tests. This study used the research and development approach from Borg and Gall. The target products or users in this study were lecturers in the sport’s physical education measurement test course. The subjects in this study were all PJKR FIK Unimed students who took the sport physical education measurement test course. The findings of the small group test showed that the questionnaire product had a total score of 565, an average of 28.25, and a total percentage of 70.62% in a small trial with a fairly valid category (used). The product could thus be used in this study, but the authors chose to carry out a large group trial to validate the product. Based on the findings of the large group test, the product questionnaire has a total score of 1369, an average of 34.22, and an overall percentage of 85.56% in a small trial with a very valid (used) category. Paired T-test employed to validate the product. Tcount = 5.11 determined from the findings of the calculation of the effectiveness test data. Pricing t-table = 2.08 calculated from the distribution list t using probability 1- = 0.95 and dk n-1 (30-1) = 1. This is mean there is an effect of learning media on interactive multimedia - sport-based measurement test, so that t count t table. It can be concluded that the interactive sports measurement test learning media in this study are well developed, valid, and effective to improve sport measurement test learning outcome.